Sodium-ion battery positive electrode material with single crystal morphology and preparation method and application of sodium-ion battery positive electrode material

By using co-doping modification of B and Bi elements and titanium dioxide coating technology in sodium electropositive electrode materials, the problem of structural instability of single crystal morphological materials during charging and discharging is solved, and higher cycle life and electrochemical performance are achieved.

CN119812309AActive Publication Date: 2025-04-11GEM WUXI ENERGY MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510015816.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Most of the existing NiFeMn series sodium electropositive electrode materials are single crystal-like morphology, which leads to crystal microcracks that may occur under deep charging state, resulting in poor electrochemical performance.

Method used

The co-doping modification was performed using elements B and Bi as doping elements to prepare a sodium ion battery positive electrode material with a single crystal morphology, and titanium dioxide was coated on the surface of the material.

Benefits of technology

By forming a positive electrode material with a single crystal morphology, the occurrence of intergranular cracks is avoided, and the cycle life and electrochemical properties of the material are improved, including discharge specific capacity, rate performance and cycle retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812309A_ABST
    Figure CN119812309A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, in particular to a sodium ion battery positive electrode material with single crystal morphology and a preparation method and application thereof. The sodium ion battery positive electrode material with the single crystal morphology comprises a material with a chemical formula of NawNixFeyMn1-x-y-z-aBzBiaO2, wherein w is less than or equal to 0.75, x is greater than 0 and less than 0.25, y is greater than 0 and less than 0.3, z is greater than 0 and less than 0.05, and a is greater than 0 and less than 0.05. According to the preparation method disclosed by the invention, the B and Bi elements are adopted for co-doping modification, so that the prepared positive electrode material has a single-crystal morphology, and the problem of performance degradation caused by crystal boundary breakage is avoided, so that the sodium-electric ternary positive electrode material with the single-crystal morphology prepared by the preparation method disclosed by the invention can still keep good structural integrity after multiple cycles, and the cycle life is prolonged. Meanwhile, the specific discharge capacity, the rate capability, the cycle retention rate and other electrochemical properties of the sodium-electric ternary positive electrode material are also remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a single crystal sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Compared with ternary positive electrode materials with polycrystalline structures, ternary positive electrode materials with single crystal structures can achieve higher compaction density, thus bringing higher energy density. Secondly, single crystal materials have better mechanical properties and will not break during the processing of electrode sheets. During the battery cycle, they will not produce obvious mechanical cracks due to high internal stress. However, the sintering products of the NiFeMn series of sodium electric materials are currently mainly single-crystal-like materials. Although single-crystal-like positive electrode materials can exhibit single-crystal-like performance at a macroscopic level, there are still a small number of grain boundaries or defects at a microscopic level. Under deep charging conditions, single-crystal-like positive electrode materials may have crystal microcracks, which are caused by structural instability caused by anisotropic lattice contraction, resulting in the electrolyte infiltration and erosion of the secondary particles, leading to serious side reactions, and then resulting in poor electrochemical performance of the positive electrode material. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defect that most of the existing NiFeMn series sodium battery positive electrode materials are single-crystal morphology, resulting in poor electrochemical performance, thereby providing a single-crystal morphology sodium ion battery positive electrode material and its preparation method and application to solve the above problem.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] In a first aspect, the present invention provides a single crystal sodium ion battery positive electrode material, which comprises a chemical formula of Na w Ni x Fe y Mn 1-x-y-z-a B z Bi a O2 material, wherein w≤0.75, 0<x<0.25, 0<y<0.3, 0<z<0.05, 0<a<0.05.

[0006] Preferably, the sodium ion battery cathode material is a core-shell structure having a core and a coating layer, wherein the core is a chemical formula of Na w Ni x Fe y Mn 1-x-y-z-a B z Bi a The material of O2 is titanium dioxide.

[0007] Preferably, the mass ratio of the core to the coating layer is 100:(0.5-2).

[0008] In a second aspect, the present invention also provides a method for preparing the above-mentioned single crystal morphology of a sodium ion battery positive electrode material, comprising: w Ni x Fe y Mn 1-x-y-z-a B z Bi a The stoichiometric ratio of the O2 material comprises weighing a sodium source, a nickel source, an iron source, a manganese source, a boron source and a bismuth source respectively and mixing them evenly to obtain a mixed material; the mixed material is subjected to a first sintering treatment to obtain a single crystal morphology of a sodium ion battery positive electrode material.

[0009] Preferably, the sodium source comprises Na2CO3;

[0010] And / or, the nickel source comprises NiO;

[0011] and / or, the iron source comprises Fe2O3;

[0012] and / or, the manganese source comprises MnO2;

[0013] And / or, the boron source comprises H3BO3;

[0014] And / or, the bismuth source includes Bi2O3.

[0015] Preferably, the mixing process lasts for 20-50 minutes;

[0016] And / or, the atmosphere of the first sintering treatment is an oxygen-containing atmosphere; optionally, the oxygen-containing atmosphere is air and / or oxygen;

[0017] And / or, the heat treatment system of the first sintering treatment is: firstly heating the temperature to 600-800°C at a heating rate of 2-5°C / min for pre-sintering for 4 hours, then heating the temperature to 950-1000°C at a heating rate of 2-5°C / min for roasting for 10-15 hours, and then cooling naturally with the furnace;

[0018] And / or, after the first sintering process, crushing and screening processes are further performed.

[0019] Preferably, the sintered material obtained after the first sintering treatment is further mixed with titanium dioxide and subjected to a second sintering treatment.

[0020] Preferably, the mass ratio of the sintering material to titanium dioxide is 100:(0.5-2);

[0021] And / or, the heating rate of the second sintering treatment is 3°C / min;

[0022] And / or, the temperature of the second sintering treatment is 700° C.;

[0023] And / or, the heat preservation time of the second sintering treatment is 8 hours;

[0024] And / or, the atmosphere of the second sintering treatment is an oxygen-containing atmosphere; optionally, the oxygen-containing atmosphere is air and / or oxygen.

[0025] Preferably, after the second sintering treatment, the product is further subjected to natural cooling in the furnace, crushing and iron removal by screening.

[0026] In a third aspect, the present invention also provides the use of the above-mentioned single-crystalline sodium-ion battery positive electrode material or the single-crystalline sodium-ion battery positive electrode material prepared by the above-mentioned method for preparing the single-crystalline sodium-ion battery positive electrode material in sodium-ion batteries.

[0027] The technical solution of the present invention has the following advantages:

[0028] 1. The present invention provides a single crystal sodium ion battery positive electrode material, which includes a chemical formula of Na w Ni x Fe y Mn 1-x-y-z-a B z Bi a O2 material, wherein w≤0.75, 0<x<0.25, 0<y<0.3, 0<z<0.05, 0<a<0.05. In order to solve the problem that most of the current NiFeMn series sodium positive electrode materials are of a quasi-single crystal morphology, the present invention uses B and Bi elements as doping elements for co-doping modification, so that the prepared positive electrode material can form a single crystal morphology. Since there is no grain boundary inside the formed single crystal material, it is not easy to have intercrystalline cracks during the charge and discharge process, thereby avoiding the performance degradation problem caused by grain boundary crushing, so that the sodium electric ternary positive electrode material with a single crystal morphology prepared by the present invention can still maintain good structural integrity after multiple cycles, thereby improving the cycle life. At the same time, the electrochemical properties of the sodium electric ternary positive electrode material of the present invention, such as discharge specific capacity, rate performance and cycle retention rate, have also been significantly improved.

[0029] 2. In the single crystal morphology of the sodium ion battery positive electrode material of the present invention, in order to further improve the electrochemical properties of the positive electrode material, titanium dioxide is coated on the surface of the single crystal morphology sodium ion battery positive electrode material, thereby effectively inhibiting the side reaction between the positive electrode material and the electrolyte, reducing the charge transfer impedance, and thus further improving the electrochemical properties of the positive electrode material such as cycle stability and rate.

[0030] 3. In the method for preparing the single crystal morphology of the sodium ion battery positive electrode material of the present invention, the sodium ion battery positive electrode material is prepared by a solid phase sintering method, which is simple to operate and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 is a SEM morphology image of a sintered material in Example 1 of the present invention;

[0033] Figure 2 is a SEM morphology image of a sintered material in Example 2 of the present invention;

[0034] Figure 3 is a SEM morphology image of a sintered material in Example 3 of the present invention;

[0035] Figure 4 This is a SEM morphology of the calcined material in Comparative Example 1 of the present invention;

[0036] Figure 5 This is a SEM morphology of the calcined material in Comparative Example 2 of the present invention;

[0037] Figure 6 It is the SEM morphology of the sintered material in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0040] Example 1

[0041] This embodiment provides a method for preparing a single crystal sodium ion battery positive electrode material, and the specific steps are as follows:

[0042] 1) According to Na0.70 Ni 0.2 Fe 0.25 Mn 0.53 B 0.01 Bi 0.01 Stoichiometric ratio of O2 Weigh H3BO3, NiO, Fe2O3, MnO2, Bi2O3, and Na2CO3 respectively, put them into a high-speed mixer and mix them for 30 minutes;

[0043] 2) The mixture was placed in an air atmosphere and heated to 750°C at a heating rate of 3°C / min for pre-calcination for 4 hours, and then heated to 950°C at a heating rate of 3°C / min for roasting for 12 hours. After cooling naturally, it was crushed and passed through a 325-mesh sieve to obtain Na 0.70 Ni 0.2 Fe 0.25 Mn 0.53 B 0.01 Bi 0.01 O2 fired material, its microscopic morphology is as follows Figure 1 As shown;

[0044] 3) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.53 B 0.01 Bi 0.01 The O2-sintered material and TiO2 in a mass ratio of 100:1 are weighed and mixed, placed in an air atmosphere and heated to 700°C at a heating rate of 3°C / min for sintering for 8 hours, cooled to room temperature, and passed through a 325-mesh sieve and iron removed to obtain the sodium battery positive electrode material.

[0045] Example 2

[0046] This embodiment provides a method for preparing a single crystal sodium ion battery positive electrode material, and the specific steps are as follows:

[0047] 1) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.51 B 0.02 Bi 0.02 Stoichiometric ratio of O2 Weigh H3BO3, NiO, Fe2O3, MnO2, Bi2O3, and Na2CO3 respectively, put them into a high-speed mixer and mix them for 50 minutes;

[0048] 2) The mixture was placed in an air atmosphere and heated to 800°C at a heating rate of 5°C / min for pre-calcination for 4 h, then heated to 1000°C at a heating rate of 5°C / min for calcination for 10 h. After cooling naturally, the mixture was crushed and passed through a 325-mesh sieve to obtain Na 0.70 Ni0.2 Fe 0.25 Mn 0.51 B 0.02 Bi 0.02 O2 fired material, its microscopic morphology is as follows Figure 2 As shown;

[0049] 3) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.51 B 0.02 Bi 0.02 The mass ratio of O2-sintered material to TiO2 is 100:0.5, weighed and mixed, placed in an air atmosphere and heated to 700°C at a heating rate of 5°C / min for sintering for 8 hours, cooled to room temperature, passed through a 325-mesh sieve and iron was removed to obtain the sodium positive electrode material.

[0050] Example 3

[0051] This embodiment provides a method for preparing a single crystal sodium ion battery positive electrode material, and the specific steps are as follows:

[0052] 1) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.47 B 0.04 Bi 0.04 Stoichiometric ratio of O2 Weigh H3BO3, NiO, Fe2O3, MnO2, Bi2O3, and Na2CO3 respectively, put them into a high-speed mixer and mix them for 20 minutes;

[0053] 2) The mixture was placed in an air atmosphere and heated to 600°C at a heating rate of 2°C / min for pre-calcination for 4 hours, and then heated to 950°C at a heating rate of 2°C / min for roasting for 15 hours. After cooling naturally, it was crushed and passed through a 325-mesh sieve to obtain Na 0.70 Ni 0.2 Fe 0.25 Mn 0.47 B 0.04 Bi 0.04 O2 fired material, its microscopic morphology is as follows Figure 3 As shown;

[0054] 3) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.47 B 0.04 Bi 0.04The O2-sintered material and TiO2 in a mass ratio of 100:2 are weighed and mixed, placed in an air atmosphere and heated to 700°C at a heating rate of 2°C / min for sintering for 8 hours, cooled to room temperature, and passed through a 325-mesh sieve and iron removed to obtain the sodium battery positive electrode material.

[0055] Example 4

[0056] This embodiment provides a method for preparing a single crystal sodium ion battery positive electrode material, which differs from Embodiment 1 in that titanium dioxide coating is not performed (ie, step 3 is not performed), and other conditions are the same as those in Embodiment 1.

[0057] Comparative Example 1

[0058] This comparative example provides a method for preparing a single crystal sodium ion battery positive electrode material, and the specific steps are as follows:

[0059] 1) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.55 O2 stoichiometric ratio Weigh NiO, Fe2O3, MnO2, and Na2CO3 respectively and mix them in a high-speed mixer for 30 minutes;

[0060] 2) The mixture was placed in an air atmosphere and heated to 750°C at a heating rate of 3°C / min for pre-calcination for 4 hours, and then heated to 950°C at a heating rate of 3°C / min for roasting for 12 hours. After cooling naturally, it was crushed and passed through a 325-mesh sieve to obtain Na 0.70 Ni 0.2 Fe 0.25 Mn 0.55 O2 fired material, its microscopic morphology is as follows Figure 4 As shown;

[0061] 3) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.55 The O2-sintered material and TiO2 in a mass ratio of 100:1 are weighed and mixed, placed in an air atmosphere and heated to 700°C at a heating rate of 3°C / min for sintering for 8 hours, cooled to room temperature, and passed through a 325-mesh sieve and iron removed to obtain the sodium battery positive electrode material.

[0062] Comparative Example 2

[0063] This comparative example provides a method for preparing a single crystal sodium ion battery positive electrode material, and the specific steps are as follows:

[0064] 1) According to Na 0.70 Ni 0.2 Fe 0.25Mn 0.53 B 0.02 Stoichiometric ratio of O2 Weigh H3BO3, NiO, Fe2O3, MnO2, and Na2CO3 respectively, put them into a high-speed mixer and mix them for 30 minutes;

[0065] 2) The mixture was placed in an air atmosphere and heated to 750°C at a heating rate of 3°C / min for pre-calcination for 4 hours, and then heated to 950°C at a heating rate of 3°C / min for roasting for 12 hours. After cooling naturally, it was crushed and passed through a 325-mesh sieve to obtain Na 0.70 Ni 0.2 Fe 0.25 Mn 0.53 B 0.02 O2 fired material, its microscopic morphology is as follows Figure 5 As shown;

[0066] 3) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.53 B 0.02 The O2-sintered material and TiO2 in a mass ratio of 100:1 are weighed and mixed, placed in an air atmosphere and heated to 700°C at a heating rate of 3°C / min for sintering for 8 hours, cooled to room temperature, and passed through a 325-mesh sieve and iron removed to obtain the sodium battery positive electrode material.

[0067] Comparative Example 3

[0068] This comparative example provides a method for preparing a single crystal sodium ion battery positive electrode material, and the specific steps are as follows:

[0069] 1) According to Na 0.70 Ni 0.2 Fe 0.25 Mn 0.53 Bi 0.02 Stoichiometric ratio of O2 Weigh H3BO3, NiO, Fe2O3, MnO2, and Na2CO3 respectively, put them into a high-speed mixer and mix them for 30 minutes;

[0070] 2) The mixture was placed in an air atmosphere and heated to 750°C at a heating rate of 3°C / min for pre-calcination for 4 hours, and then heated to 950°C at a heating rate of 3°C / min for roasting for 12 hours. After cooling naturally, it was crushed and passed through a 325-mesh sieve to obtain Na 0.70 Ni 0.2 Fe 0.25 Mn 0.53 Bi 0.02 O2 fired material, its microscopic morphology is as follows Figure 6 As shown;

[0071] 3) According to Na0.70 Ni 0.2 Fe 0.25 Mn 0.53 Bi 0.02 The O2-sintered material and TiO2 in a mass ratio of 100:1 are weighed and mixed, placed in an air atmosphere and heated to 700°C at a heating rate of 3°C / min for sintering for 8 hours, cooled to room temperature, and passed through a 325-mesh sieve and iron removed to obtain the sodium battery positive electrode material.

[0072] Test Example 1

[0073] The sodium ion battery positive electrode materials prepared in the above examples 1-3 and comparative examples 1-3 were used as the main materials for electrical performance testing. The electrical performance test conditions were: 95 (main material): 2.5 (PVDF): 2.5 (SP) mass ratio was used for homogenization (N-methylpyrrolidone was used as a dispersant (the amount of dispersant was 10 times the mass of PVDF)) and coated to form a pole piece (coating amount was 6 mg / cm 2 ), with metallic sodium as the counter electrode, glass fiber as the separator, 1 mol / L NaPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio 1:1) solution as the electrolyte, and the positive electrode sheet, sodium sheet, separator, gasket and spring are placed in a button cell to assemble a CR2032 button cell.

[0074] The button cell was placed in the Blue Electric test system for electrical performance testing. The electrical performance test parameters were set as follows: voltage range 2.0V-4.5V, the first cycle was 0.1C / 0.1C charge and discharge for capacity testing, and the discharge specific capacity (0.1C) was obtained, and then the rate performance was evaluated by 0.2C / 0.2C, 0.5C / 0.5C, and 1C / 1C charge and discharge tests, and the rate performance = discharge capacity at 1C rate / discharge capacity at 0.1C rate; finally, the cycle performance was evaluated by 1C / 1C cycle 50 times, and the capacity retention rate after 50 cycles was obtained. The test results are shown in Table 1.

[0075] Table 1

[0076]

[0077] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A single crystal sodium ion battery positive electrode material, characterized in that: It includes the chemical formula Na w Ni x Fe y Mn 1-x-y-z-a B z Bi a O2 material, wherein w≤0.75, 0<x<0.25, 0<y<0.3, 0<z<0.05, 0<a<0.

05.

2. The sodium ion battery positive electrode material according to claim 1, characterized in that The sodium ion battery positive electrode material is a core-shell structure having a core and a coating layer, wherein the core is a chemical formula of Na w Ni x Fe y Mn 1-x-y-z-a B z Bi a The material of O2 is titanium dioxide.

3. The sodium ion battery positive electrode material according to claim 2, characterized in that The mass ratio of the core to the coating layer is 100:(0.5-2).

4. A method for preparing a single crystal sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: include: According to Na w Ni x Fe y Mn 1-x-y-z-a B z Bi a The stoichiometric ratio of the O2 material comprises weighing a sodium source, a nickel source, an iron source, a manganese source, a boron source and a bismuth source respectively and mixing them evenly to obtain a mixed material; the mixed material is subjected to a first sintering treatment to obtain a single crystal morphology of a sodium ion battery positive electrode material.

5. The preparation method according to claim 4, characterized in that: The sodium source includes Na2CO3; And / or, the nickel source comprises NiO; and / or, the iron source comprises Fe2O3; and / or, the manganese source comprises MnO2; And / or, the boron source comprises H3BO3; And / or, the bismuth source includes Bi2O3.

6. The preparation method according to claim 4 or 5, characterized in that: The mixing time is 20-50 minutes; And / or, the atmosphere of the first sintering treatment is an oxygen-containing atmosphere; optionally, the oxygen-containing atmosphere is air and / or oxygen; And / or, the heat treatment system of the first sintering treatment is: firstly heating the temperature to 600-800°C at a heating rate of 2-5°C / min for pre-sintering for 4 hours, then heating the temperature to 950-1000°C at a heating rate of 2-5°C / min for roasting for 10-15 hours, and then cooling naturally with the furnace; And / or, after the first sintering process, crushing and screening processes are further performed.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The sintered material obtained after the first sintering treatment is mixed with titanium dioxide and subjected to a second sintering treatment.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the sintering material to titanium dioxide is 100:(0.5-2); And / or, the heating rate of the second sintering treatment is 3°C / min; And / or, the temperature of the second sintering treatment is 700° C.; And / or, the heat preservation time of the second sintering treatment is 8 hours; And / or, the atmosphere of the second sintering treatment is an oxygen-containing atmosphere; optionally, the oxygen-containing atmosphere is air and / or oxygen.

9. The preparation method according to claim 7 or 8, characterized in that: After the second sintering treatment, the product is naturally cooled in the furnace, crushed and screened to remove iron.

10. Use of the single-crystalline sodium-ion battery positive electrode material according to any one of claims 1 to 3 or the single-crystalline sodium-ion battery positive electrode material prepared by the preparation method of the single-crystalline sodium-ion battery positive electrode material according to any one of claims 4 to 9 in sodium-ion batteries.

Citation Information

Patent Citations

  • Small-particle single-crystal-like positive electrode material for sodium-ion battery, precursor and preparation method of small-particle single-crystal-like positive electrode material

    CN117263263A

  • Positive electrode material, preparation method thereof and sodium ion battery

    CN117766747A